Serological evidence of exposure to Bartonella sp. in dogs with suspected vector-borne diseases, toxoplasmosis and neosporosis - Gonçalves, Luiz Ricardo; Merino, Márcia Mariza Gomes Jusi; Freschi, Carla Roberta; Fernandes, Simone de Jesus; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (FapUNIFESP (SciELO), 2022)
Bartonellosis is a vector-borne zoonotic disease with worldwide distribution that infect a broad spectrum of mammalian species. Despite the recent studies carried out in Brazil, information regarding Bartonella in dogs are scarce. Therefore, we performed a retrospective study to investigate the exposure to Bartonella sp. in dogs by indirect immunofluorescence assay (IFA). Three hundred and thirty-five archived serum samples from dogs previously tested for vector-borne pathogens, Toxoplasma gondii, and Neospora caninum were screened for the presence of IgG antibodies to Bartonella sp. All dogs originated from the Metropolitan region of Ribeirão Preto, northeast of the State of São Paulo. Twenty-eight samples (8.3%) were positive for Bartonella sp. at the cut-off of 64. Among the 28 seropositive samples for Bartonella sp., 16 (57.1%) were also seropositive for Ehrlichia canis, 12 (42.8%) for Babesia vogeli, five (17.8%) for T. gondii and three (10.7%) for L. infantum and N. caninum. Our results demonstrated that dogs sampled were exposed to Bartonella sp. Since all the animals sampled in the present study were from private owners, our findings demonstrate that these people may also be exposed to Bartonella sp. Further studies designed to assess whether the infection by other arthropod-borne pathogens such as B. vogeli and E. canis are risk factors for Bartonella infection are needed.
Evidência sorológica de exposição a Bartonella sp. em cães com suspeita de doenças transmitidas por vetores, toxoplasmose e neosporose
Keywords: Brazil; canine; seroreactivity; zoonoses